ECSCW 2005 c - Gellersen, Hans.; Schmidt, Kjeld; Beaudouin-Lafon, Michel; Mackay, Wendy; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The emergence and widespread use personal computers and network technologies have seen the development of interest in the use of computers to support cooperative work. This volume presents the proceedings of the ninth European conference on Computer Supported Cooperative Work (CSCW). This is a multidisciplinary area that embraces the development of new technologies grounded in actual cooperative practices. These proceedings contain a collection of papers that reflect the variegated research activities in the field. The volume includes papers addressing novel interaction technologies for CSCW systems, new models and architectures for groupware systems, studies of communication and coordination among mobile actors, studies of cooperative work in complex settings, studies of groupware systems in actual use in real-world settings, and theories and techniques to support the development of cooperative applications. The papers present emerging technologies alongside new methods and approaches to the development of this important class of applications. The work in this volume represents the best of the current research and practice within CSCW. The collection of papers presented here will appeal to researchers and practitioners alike, as they combine an understanding of the nature of work with the possibility offered by new technologies.
Ways of the Hands -- A Design Theme for Tangible Interaction: Embodied Facilitation -- Supporting High Coupling and User-Interface Flexibility -- A Groupware Design Framework for Loosely Coupled Workgroups -- Formally Analyzing Two-User Centralized and Replicated Architectures -- Working Together Inside an Emailbox -- Emergent Temporal Behaviour and Collaborative Work -- Managing Currents of Work: Multi-tasking Among Multiple Collaborations -- The Duality of Articulation Work in Large Heterogeneous Settings $1 (Ba Study in Health Care -- Maintaining Constraints in Collaborative Graphic Systems: The CoGSE Approach -- Empirical Investigation into the Effect of Orientation on Text Readability in Tabletop Displays -- An Evaluation of Techniques for Reducing Spatial Interference in Single Display Groupware -- Cellular Phone as a Collaboration Tool that Empowers and Changes the Way of Mobile Work: Focus on Three Fields of Work -- Representations Can be Good Enough -- Using Empirical Data to Reason about Internet Research Ethics -- Community-based Learning: Design Patterns and Frameworks -- Expertise Sharing in a Heterogeneous Organizational Environment -- Local Expertise at an Emergency Call Centre -- Context Grabbing: Assigning Metadata in Large Document Collections -- Between Chaos and Routine: Boundary Negotiating Artifacts in Collaboration -- Coordination and Collaboration Environments for Production Lines: A User Acceptance Issue -- Sharing the square: Collaborative Leisure in the City Streets -- Informing Public Deliberation: Value Sensitive Design of Indicators for a Large-Scale Urban Simulation -- The Work to Make a Home Network Work.s
Keywords: Computer science; User interfaces (Computer systems).; Application software; Graphic design; Sociology; Computer Science; User Interfaces and Human Computer Interaction; Computer Appl. in Administrative Data Processing; Interaction Design; Computer Science, general; Information Systems Applications (incl. Internet).; Sociology, general; Electronic books